2021
DOI: 10.1088/1742-6596/1808/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Rice Husk Ash in Enhancing the Material Properties of Fly Ash-Based Self Compacted Geopolymer Concrete

Abstract: Concrete is a material that is needed for building construction or others is increasing. Construction increased as cement use increased. The continued use of cement will cause environmental damage, cement is the 8th largest source of carbon gas emissions in the world. One of the revolutionary developments using environmentally friendly materials as a substitute for cement is geopolymer concrete. Alternative materials rich in silica and alumina for the manufacture of geopolymer concrete, namely adding rice husk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…ASTM-C618-15 chemical standard for N, F and C classes [11] Rice husk ash has high silica content [12], [13], [14], [15], [16], [17] and has a hydrated amorphous structure. The result of XRD and XRF (Table 3) characterization of rice husk ash in Indonesia from other studies conducted in Surabaya-East Java Province [12], [16], Tangerang Regency-Banten Province [13], Aceh Besar Regency-Nangroe Aceh Darussalam Province [14], Surakarta-Central Java [15], Pekanbaru -Riau Province Sumatera [17]. The XRD characterization from Maulana et al [12] and Hadjasaputra et al [13] shows that RHA mainly consisted of amorphous silica, cristobalite, rutile, and some trace amount of montmorillonite, muscovite, and anorthite.…”
Section: Research Reviewmentioning
confidence: 99%
“…ASTM-C618-15 chemical standard for N, F and C classes [11] Rice husk ash has high silica content [12], [13], [14], [15], [16], [17] and has a hydrated amorphous structure. The result of XRD and XRF (Table 3) characterization of rice husk ash in Indonesia from other studies conducted in Surabaya-East Java Province [12], [16], Tangerang Regency-Banten Province [13], Aceh Besar Regency-Nangroe Aceh Darussalam Province [14], Surakarta-Central Java [15], Pekanbaru -Riau Province Sumatera [17]. The XRD characterization from Maulana et al [12] and Hadjasaputra et al [13] shows that RHA mainly consisted of amorphous silica, cristobalite, rutile, and some trace amount of montmorillonite, muscovite, and anorthite.…”
Section: Research Reviewmentioning
confidence: 99%
“…After a 48-hour curing period at 60±2ºC, all samples were kept in storage at 23±2ºC until further analysis The results demonstrated that waste glass powder could be used to make geopolymer pastes with 34-48 MPa 7-d compressive strengths instead of fly ash. [17].Rheological studies revealed that the composite pastes had a yield stress that was nearly twice as high as fly ash paste, suggesting that the pastes were quite stiff when slag addition exceeded 25 weight percent. The hardened pastes' compressive strength decreased with increasing water-binder ratio, whereas it increased with increasing slag content and activator dosage.…”
Section: Introductionmentioning
confidence: 97%
“…SCGC is a new concrete which fulfills the properties of both GPC and SCC. Sari et al (2021) concluded effectiveness of 10% RHA replacement in FA based SCGC (10) . N. Vishnu (2021) assessed the workability and mechanical properties of ambient cured SCGC blended with FA, GGBFS, Wollastonite, Graphene oxide (11) .…”
Section: Introductionmentioning
confidence: 97%